Nanometric dual-comb ranging using photon-level microcavity solitons - Zihao Wang; Yifei Wang; Baoqi Shi; Wei Sun; Changxi Yang; Junqiu Liu; Chengying Bao (Nature Communications)
Abstract Laser-based absolute distance measurement with low return power, fast measurement speed, high precision, and immunity to intensity fluctuations is highly demanded in applications spanning from nanotechnology to satellite formation. However, achieving all these objectives simultaneously remains a significant challenge for miniaturized systems. Here, we demonstrate dual-comb ranging (DCR) that encompasses all these capabilities by using a coherent soliton pair generated in an integrated microresonator. We derive equations linking the DCR precision with comb line powers, revealing the advantage of microcomb’s large line spacing in precise ranging quantitatively. Leveraging the advantage, our system reaches 1-nm-precision and measures nm-scale vibration at frequencies up to 0.9 MHz. Precise DCR is possible even in the presence of strong intensity noise and loss, using a mean received photon number as low as 5.5 × 10−4 per pulse (total 0.9 million photons in a single measurement considering the high repetition rate). Our work establishes an optimization principle for dual-comb systems and bridges high performance ranging with foundry-manufactured photonic chips.